Distal Biceps Reconstruction With Achilles Tendon Allograft Using Transosseous Suture Fixation - Tyler R. Mange, M.D.; Ryan S. Beyer, B.S.; Misha H. Seifi, B.S.; Tyler R. Johnston, M.D., M.S.; Jesse D. Kaplan, M.D. (Arthroscopy Techniques)
Given the biceps brachii muscle’s importance for upper-extremity function, particularly forearm supination strength and elbow flexion, operative treatment of distal biceps tendon ruptures is typically strongly considered. When primary tendon repair is not possible, multiple surgical techniques exist for reconstruction of the distal biceps insertion. These techniques vary in terms of both fixation options and graft choices. In this article, we describe a technique for distal biceps reconstruction using Achilles tendon allograft, secured to the radius via bone tunnels, that requires no specialized equipment and restores the anatomic distal biceps insertion. This technique is therefore broadly applicable and results in a consistent, robust reconstruction to restore forearm supination strength throughout the range of motion.